"SEEING" THE PAST: TEXT AND QUESTIONS OF HISTORY IN THE RĀJATARAṄGIṆĪ. Issue 2 (May 2014) - KAUL, SHONALEEKA
ABSTRACT Traditional scholarly opinion has regarded Kalhaṇa's Rājataraṅgiṇī, the twelfth‐century Sanskrit chronicle of Kashmiri kings, as a work of history. This essay proposes a reinvestigation of the nature of the iconic text from outside the shadow of that label. It first closely critiques the positivist "history hypothesis, " exposing its internal contradictions over questions of chronology, causality, and objectivity as attributed to the text. It then argues that more than an empiricist historical account that modern historians like to believe it is—in the process bracketing out integral rhetorical, mythic, and didactic parts of the text—the Rājataraṅgiṇī should be viewed in totality for the kāvya (epic poem) that it is, which is to say, as representing a specific language practice that sought to produce meaning and articulated the poet's vision of the land and its lineages. The essay thus urges momentarily reclaiming the text from the hegemonic but troubled understanding of it as history—only to restore it ultimately to a more cohesive notion of historicality that is consistent with its contents. Toward this end, it highlights the concrete claim to epistemic authority that is asserted both by the genre of Sanskrit kāvya generally and by the Rājataraṅgiṇī in particular, and their conception of the poetic "production" of the past that bears a striking resonance with constructivist historiography. It then traces the intensely intertextual and value‐laden nature of the epistemology that frames the Rājataraṅgiṇī into a narrative discourse on power and ethical governance. It is in its narrativity and discursivity—its meaningful representation of what constitutes "true" knowledge of time and human action—that the salience of the Rājataraṅgiṇī may lie.